A Study on Melatonin Administration and its Influence on Required Dose of Propofol for Anesthesia Induction in Perioperative Patients - Thota, Geetha Bhavani; Sindhura, Munagapati; Gooty, Sunanda (West Kazakhstan Medical Journal, 2025)
Melatonin, a hormone synthesized by the pineal gland has been demonstrated to promote anesthetic effect when co-administered with propofol. This led to examining the possible role of melatonin in the field of anesthesia, prompting further investigation of its use as an anesthetic adjuvant. In this study, we evaluated the minimal dose of propofol required for anesthetic induction following pre-medication with melatonin in perioperative patients. A clinical study was conducted on 60 patients, aged between 18 and 60 years who were enrolled for various surgical requirements at a tertiary care hospital, in South India. Enrolled patients were divided into two groups and designated as control (without melatonin) and treatment (with melatonin). A 3 mg/Kg melatonin tablet was administered to the melatonin group followed by a pre-determined dose of propofol intravenously, whereas the control group received B-complex followed by propofol. The results indicate administration of melatonin 3 mg as a premedication before the surgery significantly reduced the required dose of the anesthetic drug propofol when compared to the control group. Therefore, supplementation of 3 mg oral melatonin proved to be an effective premedication, offering potential benefits in both sedation and as an adjunct to the commonly used anesthetic induction agent propofol. This study provided initial evidence suggesting that pre-medication with melatonin may influence the dose of propofol required for induction. The observed reduction in propofol dose in the melatonin group has potential implications for optimizing anesthesia induction, potentially contributing to improved patient safety and resource utilization.